TYROSINE KINASE INHIBITORS AND INTERFERON - Dimou, Maria; Panagiotidis, Panagiotis (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
The use of interferon-a (INF) in chronic myeloid leukemia, when it started in the 80s, was considered as a breakthrough in the therapy of this disease; INF administered alone or in combination with aracytine was the standard choice for treatment for Chronic Myeloid Leukemia (CML) patients unfit for bone marrow transplantation. With the appearance of the first Tyrosine Kinase Inhibitor (TKI) (imatinib) and based on the results of the pivotal IRIS trial, imatinib monotherapy was the new treatment of choice for CML, according to the ELN recommendations. The possibility of combining INF with imatinib, for obtaining better therapeutic responses in CML patients has been already tested and reported. The current challenge is the combined use of second generation TKIs with pegylated –IFN, in order to minimize failures to therapy and increase the number of CML patients with deep molecular responses, who may be able to discontinue lifelong treatment.